10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Suicide is a leading cause of adolescent death in the United States (US), with access to lethal means significantly increasing mortality risk. Parents are crucial to prevention but often lack knowledge and confidence in lethal means restriction (LMR). Despite evidence-based support and national guidelines, LMR counseling remains inconsistently implemented in outpatient settings. PURPOSE: This project evaluated the feasibility, acceptability, and impact of the Lock and Protect (L&P) online decision aid in an outpatient mental health clinic, examining parent-reported changes in lethal means storage practices. METHODS: A 12-week quality improvement project was conducted in a suburban southeastern US outpatient mental health clinic. Parents and guardians of adolescents accessed the L&P decision aid via QR-code flyers during visits or through electronic health record portal messages. Participants completed anonymous surveys assessing the tool's usefulness, approachability, relevance, and planned storage practice changes. Descriptive statistics were used to analyze responses. RESULTS: Of 165 families invited, 31 completed surveys (18.8%), with in-person QR-code distribution yielding higher engagement than electronic messaging. Most participants found the tool useful (83.9%) and reported that it made discussing this difficult topic more approachable (90%). Overall, 67.7% planned to change the storage of at least one lethal means type, most commonly medications (43.3%). Among families with unsecured firearms, 66% planned to adopt more secure storage practices. CONCLUSION: Used in an outpatient mental health setting, the L&P decision aid demonstrated utility, approachability, and relevance with increased intent to secure lethal means. Findings support this LMR education as a scalable, low-burden suicide prevention strategy appropriate for outpatient practice.